In Situ Swelling Behavior of Chitosan-Polygalacturonic Acid/Hydroxyapatite Nanocomposites in Cell Culture Media - Rohit Khanna; Kalpana S. Katti; Dinesh R. Katti (International Journal of Polymer Science)
The molecular and mechanical characteristics of in situ degradation behavior of chitosan-polygalacturonic acid/hydroxyapatite (Chi-PgA-HAP) nanocomposite films is investigated using Fourier Transform Infrared spectroscopy (FTIR), Atomic Force Microscopy (AFM), and modulus mapping techniques for up to 48 days of soaking in cell culture media. The surface molecular structure of media-soaked samples changes over the course of 48 days of soaking, as indicated by significant changes in phosphate vibrations (1200–900 cm−1) indicating apatite formation. Chitosan-Polygalacturonic acid polyelectrolyte complexes (PECs) govern structural integrity of Chi-PgA-HAP nanocomposites and FTIR spectra indicate that PECs remain intact until 48 days of soaking. In situ AFM experiments on media-soaked samples indicate that soaking results in a change in topography and swelling proceeds differently at the initial soaking periods of about 8 days than for longer soaking. In situ modulus mapping experiments are done on soaked samples by probing ∼1–3 nm of surface indicating elastic moduli of ∼4 GPa resulting from proteins adsorbed on Chi-PgA-HAP nanocomposites. The elastic modulus decreases by ∼2 GPa over a long exposure to cell culture media (48 days). Thus, as water enters the Chi-PgA-HAP sample, surface molecular interactions in Chi-PgA-HAP structure occur that result in swelling, causing small changes in nanoscale mechanical properties.